2003
DOI: 10.1002/hlca.200390152
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Glycosidase Inhibitory Activities of 5‐(1′,4′‐Dideoxy‐1′,4′‐imino‐D‐erythrosyl)‐2‐methyl‐3‐furoic Acid (=5‐[(3S,4R)‐3,4‐Dihydroxypyrrolidin‐2‐yl]‐2‐methylfuran‐3‐carboxylic Acid) Derivatives: New Leads as Selective αL‐Fucosidase and β‐Galactosidase Inhibitors

Abstract: The GarcÌa-Gonza¬lez reaction of d-glucose and ethyl acetoacetate generated ethyl 5-[(1'S)-d-erythrosyl]-2-methyl-3-furoate (5), which was converted to ethyl 5-[(1'R)-1',4'-dideoxy-1',4'-imino-d-erythrosyl]-2-methyl-3-furoate (3c) and to ethyl 5-[(1'S)-1',4'-dideoxy-1',4'-imino-d-erythrosyl]-2-methyl-3-furoate (4c). Similar methods were developed to generate other carboxylic acid derivatives such as methyl (see 3e and 4e), isopropyl (see 3f), and butyl esters (see 3g), S-phenyl (see 3a) and S-ethyl thioesters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The LSI was performed using thioglycerol as the matrix. NMR and mass spectra were registered in CITIUS (University of Seville (3R,4S,5S)-5-Hydroxymethyl-3,4-O-isopropylidene-2-methyl-1-pyrroline-3,4-diol (7). To a solution of 6 (3.6 g, 8.5 mmol) in THF (20 mL), TBAF (1 M in THF, 8.5 mL, 8.5 mmol) was added.…”
Section: General Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LSI was performed using thioglycerol as the matrix. NMR and mass spectra were registered in CITIUS (University of Seville (3R,4S,5S)-5-Hydroxymethyl-3,4-O-isopropylidene-2-methyl-1-pyrroline-3,4-diol (7). To a solution of 6 (3.6 g, 8.5 mmol) in THF (20 mL), TBAF (1 M in THF, 8.5 mL, 8.5 mmol) was added.…”
Section: General Methodsmentioning
confidence: 99%
“…In recent years, we have been actively working on the development of new iminocyclitols with inhibitory activity towards α-fucosidases. [6][7][8][9] We have shown that the presence of an additional aromatic or heteroaromatic binding component close to the five membered iminocyclitol increases notably their inhibitory activity (1 10 vs. 2, 8 Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory activity of 64 towardsgalactosidase and -mannosidase is quite similar to that of A powerful inhibitior 85 against -fucosidase is similar to that of compound 63 [77,104]. Compounds with (2R,3R,4S)-configuration (86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) showed moderate inhibitory activities against -mannosidase [89], and those with a (2R,3S,4R)-configuration (98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109) tend to inhibitglucosidase and -galactosidase [88,89,93,109,110]. The specificity of these compounds was explained based on the similarity with substrate structures of individual enzymes where it was considered that a flexible pyrrolidine structure could adopt a 4 E conformation and 2-and 3-OH groups might mimic the hydroxyl groups of glucopyranosyl cation species (Fig.…”
Section: Cis-diol (B-type) [64777899102-108]mentioning
confidence: 68%
“…N , N′ , N″ ‐(1,3,5‐Phenylenetris(methylene))tris‐[5‐((2 R ,3 S ,4 R )‐3,4‐dihydroxypyrrolidin‐2‐yl)‐2‐methylfuran‐3‐carboxamide](3b): Acid 19 34b (88.9 mg, 0.246 mmol) was dissolved in DMF and 1,3,5‐tris(aminomethyl)benzene35 (11.5 mg, 0.07 mmol), DIPEA (43 μL, 0.246 mmol) and PyBOP (143.6 mg, 0.27 mmol) were added. The mixture was stirred overnight at room temp.…”
Section: Methodsmentioning
confidence: 99%